Mesenchymal Stem Cells Carrying Viral Fusogenic Protein p14 to Treat Solid Tumors by Inducing Cell–Cell Fusion and Immune Activation - Yao Wang; Xunlei Pang; Ruirui Li; Jiuzhou Chen; Chen Wen; Huihuang Zhu; Tingyu Long; Jianjie Li; Lijun Zheng; Youcai Deng; Junnian Zheng; Bo Xu (Research)
Background: Chimeric antigen receptor (CAR)-based immune cell therapies attack neighboring cancer cells after receptor recognition but are unable to directly affect distant tumor cells. This limitation may contribute to their inefficiency in treating solid tumors, given the restricted intratumoral infiltration and immunosuppressive tumor microenvironment. Therefore, cell–cell fusion as a cell-killing mechanism might develop a novel cytotherapy aimed at improving the efficacy against solid tumors. Methods: We constructed a fusogenic protein, fusion-associated small transmembrane (FAST) p14 of reptilian reovirus, into cancer cells and mesenchymal stem cells (MSCs), which cocultured with various colon cancer cells and melenoma cells to validate its ability to induce cell fusion and syncytia formation. RNA sequencing, quantitative reverse transcription polymerase chain reaction, and Western blot were performed to elucidate the mechanism of syncytia death. Cell viability assay was employed to assess the killing effects of MSCs carrying the p14 protein (MSCs-p14), which was also identified in the subcutaneous tumor models. Subsequently, the Tet-On system was introduced to enhance the controllability and safety of therapy. Results: Cancer cells incorporated with fusogenic protein p14 FAST from reovirus fused together to form syncytia and subsequently died through apoptosis and pyroptosis. MSCs-p14 cocultured with different cancer cells and effienctly induced cancer cell fusion and caused widespread cancer cell death in vitro. In mouse tumor models, mMSCs-p14 treatment markedly suppressed tumor growth and also enhanced the activity of natural killer cells and macrophages. Controllability and safety of MSCs-p14 therapy were further improved by introducing the tetracycline-controlled transcriptional system. Conclusion: MSC-based cytotherapy carrying viral fusogenic protein in this study kills cancer cells by inducing cell–cell fusion. It has demonstrated definite efficacy in treating solid tumors and is worth considering for clinical development.